IN THE BEGINNING WAS UNCONSCIOUS - MIKAELYAN, VLADIMIR (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
It can be assumed that evolution will allow a person to control his own organism, thereby removing him from the boundaries of time. Various states of consciousness also go through the path of mental development. The state of deep sleep, the state of sleep with dreams, as seen, are also aimed at the status of self-consciousness. Thus, unconscious states of consciousness, or the unconscious level of the psyche, must go the same path of modern I-consciousness, and also be within the boundaries of chronological time.